Chapter A presença dos dias / La presenza dei giorni - Alves, Adalberto (Studi di Traduzione Letteraria Lusofona, 2020)
La presenza dei giorni is the Italian translation of the equivalent Portuguese colletion of aphorisms A presença dos dias of Adalberto Alves. The literary work has been translated for the first time in Italian language by Elena Chiarini in this volume.